2017
DOI: 10.1177/0305735617739967
|View full text |Cite
|
Sign up to set email alerts
|

Choir singing as an activity to manage anxiety and temporomandibular disorders: Reports from a Brazilian sample

Abstract: The aim of this study was to evaluate anxiety, stress and symptoms of temporomandibular disorders (TMD) among a sample of participants that practice choir singing as a recreational activity. As the literature shows the positive effects of choir singing on mental and physical health, we hypothesized that anxiety, stress and TMD symptoms would be less frequent in the choir group when compared to participants from the general population. The choir group included 33 adults who participated weekly in a choral singi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…In these studies, there were significant findings. For example, Caetano et al (2019) found significant differences in anxiety and temporomandibular symptoms in choir and comparison groups. Qualitative observational research showed that most choral society members experienced a physical and emotional benefit from being a member of the choir (Clift and Hancox, 2001).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In these studies, there were significant findings. For example, Caetano et al (2019) found significant differences in anxiety and temporomandibular symptoms in choir and comparison groups. Qualitative observational research showed that most choral society members experienced a physical and emotional benefit from being a member of the choir (Clift and Hancox, 2001).…”
Section: Resultsmentioning
confidence: 97%
“…Observational studies examining the effectiveness of group singing on psychological and physical measures of wellbeing Caetano et al (2019) . Hancox (2001) Hopper et al (2016) …”
mentioning
confidence: 99%
“…Referring to the general benefits of choral singing, numerous researches support the idea that this activity may be adopted in order to enhance quality of life and promote mental and physical health. These are psychological benefits such as regulating the level of anxiety (Caetano, Ferreira, Mariotto, Vidal, Neufeld, dos Reis 2017), achieving a state of mindfulness (Lynch, Wilson 2018), obtaining a sense of belonging to a group (Sanal, Gorsev 2014) or about physical benefits such as the development of lung capacity, the remedy of various mental health problems, physical disabilities and intellectual disability (Dingle, Brander, Ballantyne, Baker 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The professional singers had less pain than the control group in various parts of the body but also around the jaw. The authors explained this by the fact that professional singers strengthen and relax their muscles through a routine of exercises [ 37 , 38 ]. All singers pursued a profession in addition to singing.…”
Section: Introductionmentioning
confidence: 99%